Open Borders and Their Impact: A Buddhist Perspective on Agriculture, Business, and Society in Matihani - Karn, Dipesh Kumar (NPRC Journal of Multidisciplinary Research, 2025)
Background: Matihani, a culturally rich community, presents a unique blend of Buddhist philosophical traditions integrated into education, environmental sustainability, and socio-economic development. Buddhist principles such as mindfulness, interdependence, and ethical conduct have significantly influenced the local way of life, fostering holistic growth and harmony. However, the practical application of these principles in modern development contexts remains underexplored. Objective: The study aims to analyze the role of Buddhist philosophy in promoting sustainable education, environmental conservation, and socio-economic development in Matihani. It also seeks to highlight the relevance of Buddhist teachings in addressing contemporary challenges faced by the community. Methods: Secondary data was gathered through a comprehensive review of literature, local documents, and policy records. Thematic and content analysis methods were used to analyze the data, with a focus on triangulation to ensure reliability. Findings: The study revealed that Buddhist philosophy significantly influences various aspects of community life: (i) Education: The principles of mindfulness and compassion are integrated into local teaching practices, fostering a value-based learning environment. (ii) Environmental Sustainability: The Buddhist tenet of interdependence guides community-led conservation initiatives, promoting harmony with nature. (iii) Socio-Economic Development: Ethical decision-making inspired by Buddhist values underpins local economic activities, encouraging equitable and sustainable growth. Despite these strengths, challenges such as modernization pressures, resource constraints, and gaps in policy implementation hinder the full realization of Buddhist-inspired practices. Conclusion: The study concludes that Buddhist philosophy offers a robust framework for holistic and sustainable development in Matihani. By incorporating mindfulness, interdependence, and ethical conduct, the community demonstrates the transformative potential of traditional wisdom in addressing modern challenges. Recommendations emphasize the need for policy support, capacity building, and collaborative efforts to further integrate Buddhist teachings into development strategies. Novelty: This study provides a unique interdisciplinary perspective by bridging Buddhist philosophy with contemporary development practices. It highlights how ancient wisdom can offer practical solutions to modern issues, contributing to global discussions on sustainable development and ethical living.